Tashmim Al`ab Lughawiyyah Li Ta`lim Al Lughah Al A`rabiyah Min Khilali Al-Kalimat Dzatu Ashlin A`rabiy Fi Qamus Al-Lughah Al Indunisiyyah Al Kabir Li Al Mubtadin Al Indunisiyyin Min Harfi ( R ) Ila ( Z ) - Hadil Ismail Hasan; Abdul Aziz (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2021)
هذه الدراسة تهدف إلى حصر الكلمات ذات أصل عربي في قاموس اللغة الإندونيسية الكبير (KBBI) من حرف (R) إلى حرف (Z). كما تهدف أيضا إلى وضع تلك الكلمات في تصميم ألعاب لغوية لتعليم الإندونيسيين المبتدئين. وتعتمد هذه الدراسة على المنهج الوصفي تحليلي، حيث جمع الباحث الكلمات ذات أصل عربي من حرف (R) إلى حرف (Z) من القاموس وحددها، وهذه الكلمات العربية بعد أن دخلت إلى اللغة الإندونيسية تنقسم إلى أربعة أقسام: الأول: الكلمات العربية بقيت معانيها في اللغة الإندونيسية، والثاني: الكلمات العربية اتسعت معانيها في اللغة الإندونيسية، والثالث: الكلمات العربية ضاقت معانيها في اللغة الإندونيسية، والرابع: الكلمات العربية تغيرت معانيها في اللغة الإندونيسية. وتوصلت الدراسة إلى النتيجتين الأساسيتين: الأولى: أن عدد الكلمات الإندونيسية ذات أصل عربي في القاموس من حرف (R) إلى حرف (Z) بلغ إلى مئة خمسة وخمسين كلمة. والثانية: أن من طرق الاستفادة من تلك الكلمات لتعليم الإندونيسيين المبتدئين هي ألعاب لغوية. This study aims to limit and analyze the words of Arabic origin in the big Indonesian language dictionary (KBBI) from the letter (R) to the letter (Z) and analyze it. It also aims to put those words into designing language games to teach junior Indonesians. This study relies on the descriptive analytical method, where the researcher collected words of Arabic origin from the letter (R) to the letter (Z) from the dictionary and identified and analyzed in terms of sound and significance, and these Arabic words after they entered the Indonesian language are divided into four sections: First: The Arabic words have their meanings in the Indonesian language, and the second: Arabic words have expanded their meanings in the Indonesian language, and the third: Arabic words have narrowed their meanings in the Indonesian language, and the fourth: Arabic words have changed their meanings in the Indonesian language. The study reached the two main results: The first: The number of Indonesian words of Arabic origin in the dictionary from the letter (R) to the letter (Z) amounted to a hundred fifty-five words, and it was analyzed. The second: that one of the ways to use these words to teach beginners Indonesians is language games.